STRATEGI PEMANFAATAN MEDIA SOSIAL DALAM MENINGKATKAN BRAND IMAGE PANTAI GLORYMELUR - Jundi Irwan Maulana, Jundi; Sholihul Abidin, Sholihul Abidin (SCIENTIA JOURNAL, 2023)
Instagram is a social media used by the Glory Beach management to refer information and improve branding.The formulation of the problem of this research is how to use Glory Beach Instagram, and how to increase theGlory Beach brand image through Instagram. This research uses a descriptive qualitative research approach(descriptive research). The conclusions in this study indicate that the strategy for increasing the Brand Imageof tourism places in the @GloryMelur account is carried out by implementing branding strategy steps whichinclude determining the target market, determining existing competition, determining the point of difference(DOP). Categories of content posted by the @GloryMelur account include promos, posters, job vacancyinformation, events, holiday greetings, visitor activities and views. The implementation of the branding strategycarried out by the @GloryMelur account can be seen in the categories of posts uploaded. Determining thetarget market is more targeted by posting promos and events. Determination of competition can be seenthrough posting promos and events that are not carried out by other similar tourism accounts (comparison withthe @vio-vio account), as well as points of difference (DOP) in posting @GloryMelur content, namely contentabout promos, posters, job vacancy info, events, holiday greetings